Laparoscopic evaluation of tubal factor in cases of infertility - Shetty, Shraddha K.; Shetty, Harish; Rai, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Tubal factor infertility accounts for approximately 25-35% of cases of female infertility. The evaluation of the fallopian tube is necessary to determine the management plan for infertility. Tubal patency can be diagnosed by hysterosalpingography (HSG) or laparoscopy with chromopertubation. The aim of this study was to determine the role of laparoscopy in the evaluation of tubal factor in infertile women. Methods: Fifty women presenting with complaints of primary and secondary infertility were investigated for tubal disease by laparoscopy at K. S. Hegde Charitable Hospital, Mangalore, from January 2007 to July 2008. Tubal patency was tested by chromopertubation using Methylene blue dye. Results: Thirty four (68%) patients were in primary infertility group while 16 (32%) patients were in secondary infertility group. 88% women were in the age group of 21 to 35 years. In 64% of women, the duration of infertility was between 1 to 5 years whereas 32% cases had been infertile for 6 to 10 years. Tubal pathology was detected in 64.7% cases of primary infertility and 68.7% cases of secondary infertility. Bilateral tubal occlusion was found in 8% and unilateral occlusion in 28% cases. Conclusion: Laparoscopy is an effective diagnostic tool for evaluation of tubal pathology. Laparoscopy and chromopertubation test should be recommended as a first step in the investigation of infertile women with tubal factor.